TRADISI SUMPAH SERAPAH SUKU AKIT DESA BERANCAH KABUPATEN BENGKALIS DALAM PERSPEKTIF ISLAM - Riki Sutiono (PAI RAFAH, 2019)
This research is here to reveal how Islam views a tradition carried out by the Akit tribe community in the Berancah village, Bengkalis Regency, namely the Oath Tradition. This problem was taken from the community's perception that the tradition of curses was a taboo for some people. This taboo assumption is caused by the curse contained in expletives. Curses are defined as hopes or prayers accompanied by words that result in distress or disaster to others. From these problems the researchers formulated into several questions as follows: 1. how is the form of language use and meaning of expletive oaths of the Akit tribal community in Bengkalis Village? How is the oath of the Akit tribe of the Beralis Village in Bengkalis Regency viewed from an Islamic perspective? In connection with this question, researchers used a qualitative approach that developed a phenomenological model. Data collection methods used by researchers are observation, interview, and documentation. The findings of this study indicate that the form of language use The form of expletives in this study is the Akit language, which is translated into Indonesian. The language style used tends to be sarcasm, which is a style that contains bitterness and is not pleasant to hear. The style of sarcasm is demonstrated through the use of diction which refers to bad conditions such as being eaten by crocodiles, being struck by lightning, being eaten by a land ghost, not being saved, and being eaten by a ghost pod. Dictation contained in expletives generally contain emotive and connotative meanings because it describes the feelings of the speaker. The components of expletive speech found in the Akit tribe are among them: "Eating Boye You!", "Not Save You!" "Yeng steals, right? Eaten Land Ghost ...!". The Islamic view of curses is Islam is strictly prohibited when people say or speak that is not good to other humans. This is confirmed by the authentic proposition narrated by Imam Ahmad which reads: "Man kaana yu 'minu billahi wal yaumil Akhir, fal yaqul khoiron au li yasmut". "Whoever believes in Allah SWT, he should say good or better be quiet." Imam Abu Hatim Ibn Hibban Al Busti said in his book, Raudhah A-Uqala wa Nazhah Al-Fudhala, p. 45, "People who have reason should be more silent than talk, because of how many people are sorry for talking and few are sorry for being quiet."